Implied equity duration as a measure of risk and its simultaneous endogeneity with performance in European companies. (16th March 2020) - Reis, Pedro
This work, in addition to applying the adapted implied equity duration (IED) concept through incorporating the dividends returned by the stock markets of France, Germany, Spain, Portugal and the UK, creates and tests new concepts both for firm risk and of business life expectancy, entitled the implied enterprise value duration (IEVD), for those countries. Furthermore, this article provides proof of the simultaneous endogeneity between IED and performance through recourse to a simultaneous equations system approach with 3sls and, additionally, studies the implications of company expected life, capital structure, size, market expectations, historic growth and risk both on IED and on performance. This paper reaches an IED based on dividends for European companies of 9.93 years, contributing to the existing IED paradox and confirming that IED is a risk measure. Furthermore, it concludes that IED does not provide a proxy for company life expectancy.